Comparison of blood microsampling with DBS and conventional blood collection techniques used in a midazolam biostudy. (April 2016) - Lachance, Sylvain; Théberge, Marie-Claude; Havard, Guy; Anctil, Dominique; Barrière, Olivier; Croteau, Sara; Pellerin, Brigitte; Lévesque, Ann
Background: Quantitative DBS LC–MS/MS assay for midazolam was used to compare two sample collection techniques (venipuncture and finger prick) and the midazolam concentrations measured in plasma samples, DBS and dried plasma spots.Methodology: Midazolam was extracted from DBS cards and compared with whole blood collected from usual venipuncture. Dried plasma spots were also compared with plasma. The blood volume used as well as the temperature impact during the blood and plasma deposits was evaluated. Midazolam was administrated to six healthy subjects during a clinical trial to obtained blood and plasma samples for the statistical comparison.Conclusion: The method for midazolam using DBS was validated and showed an excellent performance. Excellent correlations were observed when the same collection procedures were used.